Institutional Capacity in Clean Water Management in Jeneponto Regency - Herlina Sakawati; Sulmiah Sulmiah; Novayanti Sopia Rukmana; Widyawati Widyawati; Andi Tenri Citra Sari (Program Pascasarjana Universitas Negeri Makassar, 2019)
This study aims to analyze the institutional capacity in Jeneponto Regency in the management of clean water. The study was conducted using descriptive qualitative methods. Data collection is done through observation and interview techniques, which are strengthened from data from related institutions. The results showed that five dimensions were used to look at institutional capacity, only one dimension contributed to increasing the existing institutional capacity, namely the Social Norms, Values and Practice dimensions. And for the other four dimensions namely, individual dimensions, organizational dimensions, organizational network dimensions, and public governance dimensions still need to be improved. Institutional capacity in the management of clean water in Jeneponto Regency requires rules that govern cooperation between all agencies that have a connection in the management of clean water. The government needs to give training and education to employees.